Whole-genome resequencing identified QTLs, candidate genes and Kompetitive Allele-Specific PCR markers associated with the large fruit of Atlantic Giant (Cucurbita maxima) - Pan, Liu; Wang, Min; Yang, Yating; Chen, Chen; Dai, Haibo; Zhang, Zhiping; Hua, Bing; Miao, Minmin (Frontiers in Plant Science, 2022)
Atlantic Giant (AG) pumpkin (Cucurbita maxima) produces the world’s largest fruit. Elucidating the molecular mechanism of AG fruit formation is of scientific and practical importance. In this research, genome-wide resequencing of an F2 population produced by a cross between AG and its small-fruit ancestor Hubbard was used to identify quantitative trait loci (QTLs) and candidate genes. Transgressive segregation of fruit size-related traits was observed in the F2 population, suggesting that fruit size was a quantitative trait controlled by multiple genes. A genetic map with an average physical distance of 154 kb per marker was constructed, and 13 QTLs related to fruit size were identified using bin-map construction. RNA sequencing analysis revealed that pathways associated with assimilate accumulation into the fruit, including carbohydrate metabolism, were significantly enriched in differentially expressed genes. According to the predicted impact of mutation on the biological function of certain proteins, 13 genes were selected as candidate genes associated with fruit size, among which two phytohormone-related genes, CmaCh17G011340 (a flavin-containing monooxygenase) and CmaCh04G029660 (a leucine-rich repeat protein kinase) were chosen for further investigation. Finally, one insertion-deletion (inDel) and three single nucleotide polymorphisms (SNPs) were successfully transformed to Kompetitive Allele-Specific PCR (KASP) markers. The novel QTLs and candidate genes identified provide insights into the genetic mechanism of large fruit formation of AG, and the genetic map and tightly linked KASP markers developed in this study can be employed for marker-assisted breeding to alter fruit size of C. maxima.